Secretion of the pancreas: from the Pavlov’s elements to the present time - G. F. Korotko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present accumulation and development of modern knowledge of secretory activity of the pancreas with accent on regulation of enzyme production.Key points. I. P. Pavlov in acute, followed by chronic experiences on fistulated dogs has proved phases and regulatory mechanisms of exocrine secretion of the pancreas, its adaptation to types of ingested food, accented in enzymatic secret pattern. In development of concepts basic reflex, paracrine and humoral mechanisms of stimulation, inhibition and modulation of exocrine and endocrine secretions of enzymes by the pancreas are revealed now. The original concept of the functional nonequipotentionality of the gland and modular principle of the organization of its exocrine secretion, acute adaptation of enzyme secretion to nutritional structure of duodenal chyme are described.